Dapsone-induced severe cutaneous adverse drug reactions are strongly linked with HLA-B13: 01 allele in the Thai population - Tempark, Therdpong; Satapornpong, Patompong; Rerknimitr, Pawinee; Nakkam, Nontaya; Saksit, Niwat; Wattanakrai, Penpun; Jantararoungtong, Thawinee; Koomdee, Napatrupron; Mahakkanukrauh, Ajanee; Tassaneeyakul, Wichittra; Suttisai, Sumitra; Pratoomwun, Jirawat; et al. (Pharmacogenetics and genomics, 2017)
A previous publication in Chinese leprosy patients showed that the HLA-B*13:01 allele is a strong genetic marker for dapsone-induced drug hypersensitivity reactions, however there are no data describing whether HLA-B*13:01 is a valid marker for prediction of dapsone-induced drug hypersensitivity reactions in other ethnicities or nonleprosy patients. The aim of this study is to investigate whether there is an association between HLA genotypes and dapsone-induced severe cutaneous adverse reactions (SCARs) in Thai nonleprosy patients. HLA-B genotypes of 15 patients with dapsone-induced SCARs (11 drug reaction with eosinophilia and systemic symptoms, 4 Stevens-Johnson syndrome/toxic epidermal necrolysis), 29 control patients, and 986 subjects from the general Thai population were determined by the reverse PCR sequence-specific oligonucleotides probe. The HLA-B*13:01 allele was significantly associated with dapsone-induced SCARs compared with dapsone-tolerant controls (odds ratio: 54.00, 95% confidence interval: 7.96-366.16, P=0.0001) and the general population (odds ratio: 26.11, 95% confidence interval: 7.27-93.75, P=0.0001). In addition, HLA-B*13:01 associated with dapsone-induced SJS-TEN (OR: 40.50, 95% confidence interval: 2.78-591.01, P=0.0070) and DRESS (OR: 60.75, 95% confidence interval: 7.44-496.18, P=0.0001). This study demonstrated an association between HLA-B*13:01 and dapsone-induced SCARs including Stevens-Johnson syndrome/toxic epidermal necrolysis and drug reaction with eosinophilia and systemic symptoms in nonleprosy patients. Moreover, these results suggest that the HLA-B*13:01 allele may be a useful genetic marker for prediction of dapsone-induced SCARs in Thai and Han-Chinese populations.